Fihsbone Analysis: Challenges and Strategies for Implementing Merdeka Curriculum in Vocational High Schools - Azahar, Ridho; Hilhamsyah, Hilhamsyah; Alim, Maulina Idami; Hartati, Hartati; Dirmayani, Tiya; Ariani, Nina; Nasir, Farah Damia Mohd (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The curriculum serves as a vital foundation for educational institutions. However, the transition from the previous curriculum to the Merdeka Curriculum presents various challenges, especially at the vocational high school level. This study aims to identify the challenges and strategies in implementing the Merdeka Curriculum at SMK Negeri 2 Depok Sleman using fishbone analysis. A qualitative approach was employed, with data collected through semi-structured interviews involving vocational teachers who implement the Merdeka Curriculum, selected purposively, along with documentation as supporting evidence. Data analysis followed the Miles and Huberman model, encompassing data reduction, display, and conclusion drawing. The findings indicate that the main challenges lie in human resource preparedness, curriculum transition, and the misalignment of school programs with current industry demands. In response, the school has implemented several strategic steps, including curriculum socialization, teacher training, and industry collaboration. This research provides insights for educational institutions to develop curriculum policies and programs that meet industry needs and respond to the demands of the digital era.